The American strategy of preemptive war and international law - van Selle, Birgit (Department of Commercial Law, 2023)
The government of the United States has proven its determination to embark on a war against Iraq. U.S. officials, citing United Nations Security Council resolutions, insisted that the United States had the authority for the contemplated attack. While it might· have preferred to do so on the basis of an authorization by the United Nations Security Council, it emphasized from the outset that it would also act without consent of the Security Council. Representatives of other permanent members of the Security Council believed otherwise; that no resolution of the Security Council authorized U.S. armed action without its approval and that acting without consent of the Security Council constitutes a breach of international law. In its National Security Strategy, for instance, the United States declared, that it was prepared to engage in a preemptive war without Security Council authorization both during the current Iraq crisis and as a general rule. This paper addresses issues of international law raised by this unilateral approach. It concludes. that a unilateral war of preemption poses a violation of international law and that its legalization would not be desirable.